Las nuevas tecnologías basadas en inteligencia artificial (IA) como herramientas para el desarrollo de campañas publicitarias - Toaquiza Valiente, Jessica Elizabeth (2023)
Artificial intelligence has existed for several years, but recently, numerous AIpowered tools have emerged and are widely discussed in various areas of the creative industry. This research aims to analyze the impact of using these tools in the development of advertising campaigns. To achieve this, the processes involved in an advertising campaign were first identified, and the different AI-powered tools used in the creative industry were analyzed. Subsequently, a schematic process was created to demonstrate the effective relationship between these tools and the stages of advertising campaign development. Data was collected through interviews with various professionals in creative fields, including advertising experts who have worked with AI tools. These interviews provided information to expand concepts in the theoretical foundation and were utilized to create a reference guide that will serve as a resource for future advertising campaign development. The ultimate goal is to understand how artificial intelligence is influencing the advertising industry and how these tools can be effectively leveraged to enhance the creation of advertising campaigns.